STRATEGI PEMBELAJARAN AL-QUR`AN HADIS MENGGUNAKAN ENSIKLOPEDIA HADIS 9 IMAM BERBASIS MOBILE LEARNING: UPAYA MEMBANGKITKAN PARTISIPASI SISWA - Rahmatulloh, Rizka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Qur’an and Hadith learning requires innovative strategies to increase student participation, particularly among digital-generation learners who are familiar with technology. This study aims to analyze the implementation of a Qur’an and Hadith learning strategy using the mobile-based Encyclopedia of Hadith 9 Imams application as an effort to enhance student participation. This research employed Classroom Action Research based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The research subjects were 28 students of class XI-11 at MAN 1 Sidoarjo during the even semester of the 2025/2026 academic year. The instruments consisted of student participation questionnaires for pre-test and post-test, observation, and learning evaluation. The data were analyzed using descriptive qualitative and simple quantitative techniques through percentages, mean improvement, validity testing, reliability testing, normality testing, and the Wilcoxon test. The results showed that the instrument was valid and reliable, with a Cronbach’s Alpha value of 0.896. Since the data were not normally distributed, the hypothesis was tested using the Wilcoxon test. The Wilcoxon test result showed a significance value of 0.000 < 0.05, indicating a significant difference between the pre-test and post-test results. The average student participation increased from 45.6% to 81%, with an improvement of 35.4%. Therefore, the use of the mobile-based Encyclopedia of Hadith 9 Imams is effective in improving students’ participation, enthusiasm, and learning outcomes in Qur’an and Hadith learning.